Hubungan antara Dukungan Teman Sebaya dan Pengambilan Keputusan Karir terhadap Minat Karir Siswa Madrasah Aliyah se-Kecamatan Kebonagung - Dina Mariana; Muslikah Muslikah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of peer support and career decision-making on the career interest of Madrasah Aliyah students in Kebonagung District. Using a quantitative approach with purposive sampling, 100 respondents from two accredited private Madrasahs were involved. Three instruments were employed: Instrument A measured peer support based on Sarafino (2011) and Cutrona & Russell (1990), consisting of 4 items covering emotional, instrumental, informational, and appraisal support. Instrument B assessed career decision-making using indicators from Super’s theory (via Creed & Patton, 2004), with 4 items covering career planning, exploration, work information, and decision-making. Instrument C measured career interest based on Holland’s theory (1997), including 4 items: consistency, differentiation, congruence, and calculus. All instruments passed the validity test. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Results showed that peer support and career decision-making significantly influence students’ career interest. These findings confirm Holland’s and Super’s theoretical frameworks and highlight the essential role of peer dynamics and structured decision-making in adolescent career development.